(untitled) (Fiep Bulletin - online, 2014)
The school performs a fundamental duty in the formation of the children life habits and personality, beyond the global educative contents, she also is a great responsible for the food consumed by the students. The bad nourishment and the sedentary life style are contributing to the appearance of new co-morbidity and amongst them the excess body weight in result of the obesity. The problems of the undernourishment and the obesity in children and teenagers, in Brazil, reinforce the importance of the promotion of health actions, enlarging data about nutrition and health, offering activities that develop the eat act and what to eat. In view of the concern about the nutrition quality and consequences like the rise of the obesity, the present study aims diagnosis which food are the most consumed by the children and teenagers from private schools in the city of Fortaleza. This study is a transversal delineation study and by convenience. The sample was made in 32 private schools, during the month of September. The schools were from three different zones: south zone, downtown and north zone. To the data collect was applied a questionnaire with 5 questions about the food sold and nutritional accompaniment. The analyses of the results was trough the descriptive statistic, program SPSS 13.0. The results show us that the carbohydrates, industrialized, vitamins and proteins are offered in all the canteens. The carbohydrate group is the most consumed and the proteins group is the least consumed by the students. In a general way, the food sold in the canteen offer few resources to the period of the adolescence happen in the limits that may optimize the linear growing up. We may conclude that the canteens must increment healthier foods in the respective menus and create a conscience in parents and children about the health nutrition to a good life quality and prevention to obesity and the others dyslipidemia.